Variability in the Foraging Distribution and Diet of Cape Gannets between the Guard and Post-guard Phases of the Breeding Cycle - Botha, Jonathan A.; Pistorius, Pierre A. (Frontiers in Marine Science, 2018)
During breeding, seabirds are central place foragers and are sensitive to changes in local prey availability. As the breeding season progresses, the foraging behaviour and distribution is expected to change in response to possible changes in local prey availability. In addition adult gender, and the increasing nutritional demands of a growing chick may also influence the foraging behaviour of individuals. At present, few studies have assessed the foraging behaviour of adult birds during the late post-guard stages of chick rearing. Through a combination of GPS tracking and diet sampling we investigated the foraging distances, spatial distribution and prey composition of adult Cape gannets (Morus capensis) during the guard and post guard-stages of chick rearing. We found no clear evidence for consistent sex-specific differences in foraging behaviour and spatial distribution during the guard stage, although marginal differences in the location of core foraging areas during the post-guard stage were apparent. Results, however, revealed a clear increase in foraging range from the early guard to the late post-guard stage of chick rearing. During December the diet was comprised almost exclusively of anchovy (Engraulis encrasicolus), the proportion of which had decreased significantly in the diet by January. This was mirrored by a substantial increase in the proportion of saury (Scomberesox saurus). These results suggest that Cape gannets show flexibility in the foraging behaviour and diet, which may be related to changes in the abundance and distribution of prey or may reflect changes in the energetic requirements of the growing offspring. This study provides the first assessment of Cape gannet foraging behaviour and spatial distribution during the post-guard stage of chick rearing. The importance of considering intra-annual variability in foraging distribution when using seabird tracking data in trophic and marine spatial planning studies are highlighted.